Reducing Subspaces of the Dual Truncated Toeplitz Operator - Yinyin Hu; Jia Deng; Tao Yu; Liu Liu; Yufeng Lu (Journal of Function Spaces)
We define the dual truncated Toeplitz operators and give some basic properties of them. In particular, spectrum and reducing subspaces of some special dual truncated Toeplitz operator are characterized.